Pengaruh Dialek Bahasa Daerah Terhadap Kesalahan Fonologi dalam Bacaan Al-Qur’an - Erna Dewi (Al-Kauniyah: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
In learning a foreign language, mistakes are an inevitable learning process. However, we need to find a solution to fix this error. Phonological errors are one of the common mistakes made when reading the Quran, especially when the pronunciation of the letters is similar. Such errors are called phonetic errors (al-Akhtha' al-Lughawi) in the context of phonology of the Qur'anic reading. Regional dialects also affect phonological errors when reading the Quran. The purpose of this study is to describe and analyze the location of phonological errors when reading the Quran. This research is bibliographic and refers to research that collects data by collecting data from various documents. The approach used in this study is a qualitative approach that focuses on the use of scientific logic to analyze the dynamics of the comparative thinking process and the relationship between the observed phenomena. The type of research used in this study is descriptive research. The results of this study show that there are errors in articulation, namely consonant reading errors and vowel/annotation errors. Lack of learning tajweed, lack of application of tajweed, and lack of correct pronunciation practice when reading the Qur’an are also the causes of these errors. In addition, the dialect of the regional language also affects the way the Qur'an is read. There are several errors in the pronunciation and recitation of the Qur’an caused by inaccuracies in intonation, pronunciation of letter sounds, and the influence of regional language dialectics.